2018
DOI: 10.1007/s10548-018-0655-6
|View full text |Cite
|
Sign up to set email alerts
|

Accurate Coil Positioning is Important for Single and Paired Pulse TMS on the Subject Level

Abstract: Function-guided navigation is commonly used when assessing cortical excitability using transcranial magnetic stimulation (TMS). However, the required accuracy, stability and the effect of a change in coil positioning are not entirely known. This study investigates the accuracy of function-guided navigation for determining the hotspot. Furthermore, it evaluates the effect of a change in coil location on the single and paired pulse excitability measures: motor evoked potential (MEP) amplitude, TMS evoked potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 53 publications
4
21
0
Order By: Relevance
“…We predict that the topographic maximum of the N100 is located at the respective stimulation site, i.e., covaries with changes in coil position. We further predict that N100 amplitudes are similar in magnitude following stimulation at different positions given that cortical excitability could be equal across stimulation positions, consistent with the results of de Goede et al (2018) . Our second hypothesis concerns the cortical origin of the N100; we expect that primary motor cortex activation can be represented by a single equivalent dipole in the motor cortex.…”
Section: Introductionsupporting
confidence: 83%
See 3 more Smart Citations
“…We predict that the topographic maximum of the N100 is located at the respective stimulation site, i.e., covaries with changes in coil position. We further predict that N100 amplitudes are similar in magnitude following stimulation at different positions given that cortical excitability could be equal across stimulation positions, consistent with the results of de Goede et al (2018) . Our second hypothesis concerns the cortical origin of the N100; we expect that primary motor cortex activation can be represented by a single equivalent dipole in the motor cortex.…”
Section: Introductionsupporting
confidence: 83%
“…Our results concerning the N100 amplitude and latency as well as GFP further support the conclusion that TMS stimulated regions beyond the primary motor cortex. Exclusive activations within the primary motor cortex should yield either both N100 and GFP amplitude reduction during stimulation away from the hot spot (similar to the MEP amplitude changes) or there should be no changes in TEP amplitudes, similar to the study from de Goede et al (2018) . These authors observed no differences in TEP amplitudes across nine stimulation positions 2 or 5 mm around the hot spot within a latency of 100 ms.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…The problem of low field strength is naturally even greater when TMS is combined with EEG because the electrodes mounted in the cap cause a distance of the coil from the scalp of at least approximately 2mm, rather more. The strength of the magnetic field is maximal close to the coil surface and decreases exponentially with the distance from there (Cohen et al, 1990;de Goede et al, 2018). An interesting way to attenuate this problem might be closed--1 2 -loop stimulation, through which TMS efficacy might be enhanced by better timing relative to the ongoing oscillatory cortical activity (Bergmann et al, 2012;Kraus et al, 2016;Raco et al, 2016).…”
Section: (1) Restrictions By Closely Adjacent Target Areas and Small mentioning
confidence: 99%